Vitamin D deficiency during pregnancy in Turkey and the effect of the sunlight: a systematic review and meta-analysis - Yakar, Burkay; Kaya, Mehmet Onur (Walter de Gruyter Gmbh, 2021)
Objectives: vitamin D deficiency is a common and important problem during pregnancy. vitamin D deficiency in pregnancy can cause serious health problems for both mother and fetus. The aim of this study was to systematically review the literature for studies that assessed vitamin D status during pregnancy in the Turkey and affects of the sunlight on Vitamin D deficiency. Methods: We conducted a systematic review and meta-analysis focused on vitamin D deficiency among pregnancy. PubMed, Scopus, Web of Science and Turkey citation index databases were searched between January 2010 and October 2019 was undertaken using keywords for 'Vitamin D deficiency' and 'Pregnancy' and 'Turkey' with English language restrictions imposed. Results: A total of 66 studies were identified; 14 were included in the review. The prevalence of vitamin D deficiency in pregnancy was 83%, including all studies regardless of time in Turkey. When evaluated seasonal period, the prevalence of vitamin D deficiency was 73% in pregnant women in the sunny period, while it was 90% in the less sunny period. Conclusions: The prevalence of vitamin D deficiency is high in pregnancy and is a major public health problem in Turkey. Turkey specific strategies should be developed for reducing vitamin D deficiency prevalence by investigation of risk factors and protective factors of vitamin D deficiency.
Keywords: pregnancy; prevalence; Turkey; vitamin D deficiency